FAKTOR SISA MATERIAL YANG MEMPENGARUHI BIAYA PADA PELAKSANAAN PROYEK KONSTRUKSI GEDUNG DI PROVINSI ACEH - Julsena Julsena; Abdullah Abdullah; Anita Rauzana (Prodi Magister Teknik Sipil Unsyiah, 2018)
The material has a large percentage of 50-70% of the total project cost. Good management can reduce the occurrence of excess material waste. The remaining material that has not been identified, will make the contractor does not know what percentage of losses caused by the remaining material in the project site. This study aims to identify the dominant factors causing the residual material, and to analyze the relationship and the influence of the remaining factors of material on the cost of building construction projects in Aceh Province. This study uses a mixed method, which combines qualitative and quantitative approaches through the distribution of questionnaires. Respondents addressed to the project manager of building contractor company with sub-field BG004 ranging from medium qualification (M1, M2), and large (B1). Based on the data of Construction Services Procurement Service (LPJK) in 2017 the number of contracting companies obtained as many as 215 companies, using Slovin formula then the research sample obtained as many as 68 companies. The sampling technique used is simple random sampling, randomly regardless of the strata present in the population. Of the 68 companies selected, construction costs range from Rp. 588,000,000 up to Rp. 30,251,965,000, with implementation period from 2010-2017. Data processing consists of validity, and reliability, while data analysis consists of descriptive analysis, simple correlation and multiple linear regression through Statistical Product and Service Solution (SPSS) version 22 software. The results show that the dominant remaining material factor that occurs during project implementation building construction in Aceh Province is a residual factor with a mean of 4.729. The design, procurement, handling and implementation factors have low correlation with Spearman coefficient of 0.260, 0.295, 0.373, and 0.296, while the residual factor has a very low correlation with Spearman coefficient of 0.130 to the cost of building construction projects in Aceh Province.